FEMALE SEXUAL DYSFUNCTION - C. DADAK; M. BAYERLE-EDE (Акушерство, гинекология и репродукция, 2016)
Female sexual dysfunction affect up to 43% of women causing a "distress" or a psychological strain for the patients. A variety of chronic diseases in addition to menopause and different drugs represents the risk factors to a female sexual dysfunction. Since 2015 the FDA has approved Flibanserin for the treatment of female libido although several other drugs have been proven efficacious.